Pengembangan Desain Batik Dermo Untuk Penguatan Ekonomi Kreatif Kota Kediri - Widodo, Teguh Dwi; Raharjo, Rudianto; Bintarto, Redi; Putri, Debri Harynia; Abdullah, Harnan Malik (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
Batik products provide the second largest contribution of 20-30 percent of gross domestic product (GDP) in the creative economy sub-sector. In the sub-district of Dermo, some of its residents live from agriculture, handicrafts and the batik industry. From the team's observations, it was found that Dermo Village was the leading village for batik producing. The Batik industry is a home industry that can support a portion of the population of the Dermo Village. The development of batik is very much influenced by the design abilities of the batik makers. The batik groups in Kelurahan Dermo are mostly housewives, so the problem of design is a problem. But no less creative and innovative, handicrafts have become one of the largest creative industries in Indonesia, although they are not as sophisticated as today's electronic devices or gadgets, handicrafts are still one of the alternatives or choices of society to satisfy and please their hearts. Moreover, Indonesian handicrafts are truly unique and different, supported by many natural resources such as rattan, wood, bamboo and human resources in Indonesia, Indonesian people are freer in producing and creating handicraft products in any form, so that businesses like this can has progressed very rapidly and made Indonesian handicrafts can be shipped abroad. However, the time needed to make batik is very long, especially if people order a special motif that does not have many guidelines or examples of batik designs. So this makes batik craftsmen reluctant to accept large quantities of typical batik orders. These can reduce the confidence of consumers who want to make typical batik in large quantities. For this reason, the team tried to develop batik designs with distinctive motifs which were manifested in the form of prints. From the design development that has been done by making batik stamps with typical motifs of the City of Kediri, this is able to reduce the time for batik production and make batik craftsmen more confident in receiving orders in larger quantities than before. So that with this motif stamp, the batik production of Dermo Kediri Village can increase.